Human Resources Management in Social-Cultural Life - Syaeful Bahri (Institute of Computer Science (IOCS), 2021)
This paper aims to determine the relationship between human resource management and socio-cultural life and the role of human resource management in social development. The research method used is qualitative-descriptive in the form of library research, which focuses on the study of scientific literature, both books and journal articles. The study concludes that the relationship between human resource management and socio-cultural life has a very close bond, social life will be largely determined by the quality of its human resources, while human resource management is a system to improve the quality of human resources. In a socio-cultural perspective, quality human resources are productive, innovative, integrative, and hold tightly to social values ??and norms. So, in the process of developing human resources, humans are no longer considered as production assets or organizational slaves, but more than that, humans are considered as determinants of the quality of social life.